Clinical analysis of transurethral holmium laser enucleation in the treatment of benign prostatic hyperplasia with prostatic inflammation: A prospective research study - Zhou, Weijian; Mao, Dongdong; Li, Liang; Liu, Gang; Gao, Guojun; Li, Haikun; Gao, Dianjun (Frontiers in Surgery, 2023)
Objective: To investigate the clinical efficacy of transurethral holmium laser enucleation for the treatment of benign prostatic hyperplasia (BPH) with prostatic inflammation (PI). Methods: We prospectively collected and followed up data on patients with BPH who underwent transurethral holmium laser enucleation of the prostate (HoLEP) at the Affiliated Hospital of Weifang Medical University from July 2021 to July 2022. According to the postoperative pathological results, the patients were divided into two groups: BPH without PI group (BPH group) and BPH with PI group. Statistical analysis was performed on the clinical data, including age and body mass index (BMI), prostate volume (PV), postoperative residual urine volume (PVR), preoperative serum total prostate-specific antigen (tPSA), serum-free prostate-specific antigen (fPSA), preoperative and postoperative maximum urinary flow rate (Qmax), International Prostate Symptom Score (IPSS) before and 3 months after surgery, Quality of life index (QoL) before and 3 months after surgery and postoperative complications. Results: A total of 41 patients were included in this study, including 16 in the BPH group and 25 in the BPH with IP group. There were no significant differences in preoperative age, BMI, PV, PVR, tPSA, fPSA, and f/tPSA between the BPH and BPH with PI groups (P >0.05). In both groups, Qmax significantly increased (P <0.05), and IPSS and QoL significantly decreased after HoLEP (P <0.05). Before and after surgery, the Qmax in the BPH with PI group was lower than that in the BPH group, and the levels of IPSS and QoL in the BPH with PI group were higher than those in the BPH group (P <0.05). Compared with the BPH group, the increase in Qmax in the BPH with PI group was smaller, and the decrease in IPSS was larger (P <0.05), but the change in QoL was not statistically significant (P >0.05). Conclusion: The improvements in Qmax, IPSS, and QoL in BPH patients with PI after HoLEP surgery were lower than those in BPH patients alone. PI may be a predictor of worse response to surgical treatment. Therefore, clinicians should pay attention to the diagnosis and treatment of PI.